1990
DOI: 10.1007/bf00014103
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of planktonic ciliated protozoa in 20 subtropical Florida lakes of varying trophic state

Abstract: The planktonic ciliate populations of 20 Florida lakes ranging from oligotrophic to hypereutrophic were examined monthly for one year. Oligotrophic lakes displayed abundance peaks during fall mixis and biomass peaks in late winter and fall. Mesotrophic systems exhibited a spring-fall bimodality in ciliate abundance with a biomass maxima occurring during fall. Eutrophic/hypereutrophic lakes had pronounced abundance and biomass maxima during summer, with the large ciliates Plagiopyla nasuta and Paramecium trichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 28 publications
(40 reference statements)
6
27
0
Order By: Relevance
“…The ciliate composition to the genus level at Catemaco resembles the composition found at other shallow tropical freshwater ecosystems, such as those reported by Bagatini et al (2013) for 13 Brazilian lakes or Beaver and Crisman (1982, 1990 for eutrophic lakes in Florida. These findings may generalize to an almost cosmopolitan distribution throughout these aquatic systems (Pfister et al, 2002).…”
Section: Ciliate Assemblage Compositionsupporting
confidence: 78%
See 2 more Smart Citations
“…The ciliate composition to the genus level at Catemaco resembles the composition found at other shallow tropical freshwater ecosystems, such as those reported by Bagatini et al (2013) for 13 Brazilian lakes or Beaver and Crisman (1982, 1990 for eutrophic lakes in Florida. These findings may generalize to an almost cosmopolitan distribution throughout these aquatic systems (Pfister et al, 2002).…”
Section: Ciliate Assemblage Compositionsupporting
confidence: 78%
“…Predation, filamentous cyanobacteria, and ciliate assemblage regulation Jürgens et al (1999b) found abundant small ciliates at a temperate hypertrophic lake and determined that their (Beaver and Crisman, 1990) East Lake, USA Mesotrophic 86 (max) (Beaver and Crisman, 1990) Lake Scott, USA Eutrophic 356 (avg) (Beaver and Crisman, 1990) Lake Houhu, China Mesotrophic 35.5 (avg) (Song, 2000) Lake Nani Tal, India Eutrophic 55-116 (min-max) (Shukla and Gupta, 2001 (Havens et al, 2007), and the authors stated that fish predation must exert a stronger top-down control on the pelagic food web in subtropical lakes than in temperate lakes of similar trophic status. Catemaco's plankton assemblage is the result of selective predation pressure by planktivorous fish, which prey on the larger zooplankton, including the large non-selective daphnids that graze on cyanobacterial trichomes and consume the more edible phytoplankton species, thus leaving behind trichome-enriched water (Komárková and Tavera, 2003).…”
Section: Ciliate Assemblage Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature is another factor apparently influencing succession of ciliates. Accord− ing to Beaver and Crisman (1990) the growth and reproduction of freshwater ciliates are strongly correlated with temperature. As shown by previous research by Finlay (1980) the water temperature has additionally a significant influence on the occur− rence of groups of ciliates in significantly fertile reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, specific attention has also been addressed to the description of ciliates belonging to the planktonic and benthonic microcommunities of lakes (Bark, 1981;Madoni, 1989Madoni, , 1990Beaver & Crisman, 1990;Laybourn-Pany et al, 1990a), reservoirs (Simek et al, 1990), and rivers (Baldock & Sleigh, 1988;Grabacka 1988;Carlough & Meyer, 1989;Blatterer & Foissner, 1990;Grolière et al, 1990;Finlay et al, 1993). As far as the Italian lakes are concerned, only the ciliate communities of Lake Maggiore, Lake Orta (Ruggiu, 1965(Ruggiu, , 1969, and of an artificial lake in the Tusco-Emilian Apennines (Madoni, 1989) have been studied.…”
Section: Introductionmentioning
confidence: 99%